2022
DOI: 10.1177/10732748221129464
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of EGFR Mutations in Non-small Cell Lung Cancer in the Middle East and North Africa

Abstract: Objectives This study aims to analyze the prevalence and spectrum of epidermal growth factor receptor (EGFR) mutations within the Middle East and North Africa region, compare the findings to other parts of the world, and explore the geographic disparities of EGFR mutations across the region. Methods We conducted a literature search using the terms “[EGFR] AND [mutation] AND [Non-Small Cell Lung Cancer] AND [Middle East OR North Africa]”, using PubMed, Science Direct, Web of science, Embase, Scopus, and Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…In the population of the present study, the mutation frequency was lower than in the East Asian study but higher than the reported frequencies in the European study ( 14 , 15 ). The results obtained in the present study were similar to a recent systematic review, which revealed an overall prevalence of 17% for EGFR mutations in the Middle East and North African region; however, they reported significant variations within countries ranging from 11-30% ( 16 ). In the present study, EGFR mutations were significantly more frequent in non-smokers, with 22 out of 29 patients with EGFR positive mutations falling into this category.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the population of the present study, the mutation frequency was lower than in the East Asian study but higher than the reported frequencies in the European study ( 14 , 15 ). The results obtained in the present study were similar to a recent systematic review, which revealed an overall prevalence of 17% for EGFR mutations in the Middle East and North African region; however, they reported significant variations within countries ranging from 11-30% ( 16 ). In the present study, EGFR mutations were significantly more frequent in non-smokers, with 22 out of 29 patients with EGFR positive mutations falling into this category.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, EGFR mutations were significantly more frequent in non-smokers, with 22 out of 29 patients with EGFR positive mutations falling into this category. These findings are well reported in a number of studies ( 16-18 ); in particular, the meta-analysis by Ren et al ( 18 ) which indicated that the odds ratio for EGFR mutation in non-smokers was 4.8 compared with smokers.…”
Section: Discussionsupporting
confidence: 72%
“…The EGFR gene, with chromosomal location 7p11.2 and 32 exons, has the most mutations related to lung cancer in exons 19 and 21 (18). Most of the known mutations in these exons have been of the deletion or substitution type (21).…”
Section: Introductionmentioning
confidence: 99%